Brazil - Improving Fiscal Circumstances for Growth - Weisman, Ethan; Blanco, Fernando (World Bank, Washington, DC, 2012)
Fiscal circumstances in Brazil are a key constraint to faster and more robust economic growth. In part, this is due to accumulated public sector deficits in earlier periods that are represented in Brazil's persistently high net public sector debt (currently about 50 percent of GDP). During the 1980s and mid-1990s high debt was associated with debt crises and hyperinflation. Budget rigidity, especially revenue earmarking, restricts policy action to resolve the fiscal conundrum.